Breathable cool comfortable fabric and preparation method thereof
By using polyester-based coconut carbon fiber, polyester-based coffee carbon fiber and horn melon fiber in the fabric, and covering the surface with gel capsules and hydrophilic cationic polyester polyether block copolymer, the problem of poor hydrophilic and hygroscopicity of polyester fiber fabrics in humid and hot environments is solved, and fabrics with high breathability, cooling, antibacterial and quick-drying properties are achieved.
Patent Information
- Application Number
- CN202411612660.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
When worn in a humid and hot environment, polyester fiber fabric has poor hydrophilicity and moisture absorption, resulting in a sticky and stuffy discomfort, limiting its application in summer wear, sportswear and casual wear.
Select polyester-based coconut carbon fiber, polyester-based coffee carbon fiber and horn melon fiber to enhance the breathability and comfort of the fabric, and cover the surface of the fabric with gel capsules and one side of the hydrophilic cationic polyester polyether block copolymer to improve cooling, antibacterial and quick-drying properties.
It significantly improves the breathability and comfort of the fabric, enhances the cooling and antibacterial properties, and improves the quick-drying performance, avoiding sticky and stuffy discomfort.
Smart Images

Figure BDA0005131306820000121 
Figure BDA0005131306820000131
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fabrics, and in particular relates to a breathable, cool and comfortable fabric and a preparation method thereof. Background Art
[0002] Polyester fiber, also known as polyester fiber, is a type of synthetic fiber with excellent properties such as high modulus, good elasticity, shape retention and high heat resistance stability. It is widely used in clothing and household products. However, due to the dense stacking of polyester fiber macromolecules and high crystallinity, water molecules are difficult to penetrate and the hydrophilicity is very poor. It is a typical hydrophobic fiber with a moisture regain of only 0.4%-0.5% under standard conditions. When polyester fabric is worn in a hot and humid environment, due to its poor hydrophilicity and hygroscopicity, wet clothing easily sticks to the skin and produces a sticky and stuffy discomfort, which reduces the wearing comfort of the clothing. Its application in summer clothing, sportswear and casual wear is subject to certain restrictions. How to retain the excellent properties of polyester fiber itself and improve the moisture absorption and perspiration performance of the fabric is critical to improving the wearing comfort of polyester fabric and the wider application of polyester fiber. Summary of the invention
[0003] The object of the present invention is to provide a breathable, cool and comfortable fabric and a preparation method thereof. The present invention improves the breathability and comfort performance of the fabric by selecting polyester-based coconut carbon fiber, polyester-based coffee carbon fiber and kiwano fiber with good air permeability, comfortable texture, cooling and antibacterial properties in the fabric selection; in addition, gel capsules are covered on the surface of the fabric to further enhance the cooling and antibacterial properties of the fabric; further, a hydrophilic cationic polyester polyether block copolymer is covered on one side of the fabric to enhance the quick-drying performance of the fabric.
[0004] The technical problem to be solved by the present invention is to prepare a fabric with excellent air permeability, cool feeling and comfort.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A method for preparing a breathable, cool and comfortable fabric comprises the following steps:
[0007] S1, taking polyester-based coconut carbon fiber, polyester-based coffee carbon fiber, and kiwano fiber to mix to obtain a mixture, immersing the mixture in treatment solution A for 25-35h, fishing out and shaking, opening, carding, drawing, roving, spun yarn, winding, and obtaining warp;
[0008] S2, taking cotton fiber, cleaning, combing, drawing, roving, spun yarn, winding, and obtaining weft yarn;
[0009] S3, weaving the warp and weft into a grid shape using a loom to form a grey cloth A;
[0010] S4, immersing the grey cloth A in the treatment solution B, heating in a water bath at 90° C. for 40-50 min for alkali treatment, taking out and washing with water to obtain the grey cloth B;
[0011] S5, immersing the grey cloth B in the treatment solution C, performing padding finishing at 40° C. for 40-60 min, and baking at 120° C. for 2-3 min to obtain the grey cloth C;
[0012] S6. Coat the treatment liquid D on one side of the grey cloth C, pre-bake at 80° C. for 2-3 min, and bake at 120° C. for 5-6 min to obtain the breathable, cool and comfortable fabric.
[0013] As a preferred technical solution of the present invention, the polyester-based coconut carbon fiber (purchased from Siguan Textiles (Dongguan) Co., Ltd.) is made by carbonizing the fiber of the coconut shell and then mixing it with polyester and adding other chemical substances to make coconut carbon masterbatch, and then diluting it with polyester as a carrier to form coconut carbon long fibers. The unique special-shaped structure makes the coconut carbon fiber have extremely strong adsorption capacity, antibacterial and good moisture absorption and air permeability.
[0014] As a preferred technical solution of the present invention, the polyester-based coffee carbon fiber (purchased from Zhejiang Datong Light Textile Co., Ltd.) is made by carbonizing coffee grounds and then mixing them with polyester and adding other chemical substances to make coffee carbon masterbatch, which is then diluted with polyester as a carrier to form coffee carbon long fibers. It has a smooth and glutinous feel, soft and comfortable touch, antibacterial and deodorizing, moisture absorption and breathability and other multiple functions.
[0015] As a preferred technical solution of the present invention, the scoparia fiber (purchased from Shanghai Magic Tree Biotechnology Co., Ltd.) comes from the seeds of the scoparia plant and is a natural cellulose fiber with a cool texture and excellent air permeability, comfort and antibacterial properties.
[0016] As a preferred technical solution of the present invention, the polyester is terylene well known to those skilled in the art, and its main component is any one of polybutylene terephthalate fiber and polytrimethylene terephthalate fiber.
[0017] As a preferred technical solution of the present invention, in step S1, the mass ratio of the polyester-based coconut carbon fiber, polyester-based coffee carbon fiber, kiwano fiber, and treatment liquid A is 2-3:2-3:0.5-1:35-45.
[0018] As a preferred technical solution of the present invention, the treatment liquid A is prepared by crude oil AL-106 (purchased from Guangzhou Dow Chemical Co., Ltd.) and deionized water in a volume ratio of 1:8.5-9.2.
[0019] As a preferred technical solution of the present invention, the cotton fiber is made of Xinjiang fine-staple cotton purchased from the cotton processing plant of Luntai County Yuanjiang Agriculture, Industry and Trade Co., Ltd.
[0020] As a preferred technical solution of the present invention, in step S3, the mass ratio of the warp and weft is 7:3.
[0021] As a preferred technical solution of the present invention, in step S4, the treatment solution B is prepared from sodium chloride, sodium hydroxide and deionized water in a mass ratio of 0.5:40:1000.
[0022] As a preferred technical solution of the present invention, in step S5, the method for preparing the treatment solution C comprises the following steps:
[0023] Sodium alginate, deionized water, Span 80, peppermint oil and berry tea extract were mixed, homogenized at an emulsification speed of 10,000 rpm for 4-5 minutes, gelatin was added, the pH was adjusted to 4.2-4.4, homogenized at 45° C. at an emulsification speed of 10,000 rpm for 6-8 minutes, then cooled to 0-10° C. and allowed to stand for 0.5 hours, the pH was adjusted to 9-10, glutaraldehyde aqueous solution was added, and the mixture was allowed to stand at room temperature for 3-4 hours, polyacrylic acid was added, and stirred for 20-30 minutes to obtain the treatment solution C.
[0024] As a preferred technical solution of the present invention, the mass ratio of sodium alginate, deionized water, Span 80, peppermint oil, berry tea extract, gelatin, glutaraldehyde aqueous solution, and polyacrylic acid is 1-1.2:100:0.4-0.6:4-5:2-3:3-4:3-4:0.4-0.7; the mass fraction of the glutaraldehyde aqueous solution is 25%.
[0025] As a preferred technical solution of the present invention, the preparation method of the berry tea extract comprises the following steps:
[0026] The bud tips of berry tea are extracted with ethanol aqueous solution under ultrasound, and the solvent is removed to obtain berry tea extract; 15-25 mL of ethanol aqueous solution is added to each gram of berry tea, the extraction temperature is 50-70°C, the extraction time is 30-50 minutes, and the concentration of the ethanol aqueous solution is 55-75%.
[0027] As a preferred technical solution of the present invention, the average molecular weight of the polyacrylic acid is 2000.
[0028] As a preferred technical solution of the present invention, in step S6, the coating amount of the treatment liquid D is 15-27 g / m 2 .
[0029] As a preferred technical solution of the present invention, in step S6, the method for preparing the treatment liquid D comprises the following steps:
[0030] A1. In a nitrogen atmosphere, add dimethyl terephthalate, ethylene glycol and zinc acetate to a four-necked flask equipped with a thermometer, heat at 140-150°C for 30-40 minutes, heat to 180°C and stir for 3-4 hours, add polyethylene glycol 2000, di(hydroxyethyl)methyl dodecyl ammonium chloride and antimony trioxide, slowly heat to 220-240°C, keep warm for 30 minutes, apply vaseline on the interface of the device to ensure the sealing of the device and start evacuating to vacuum. The temperature is -0.05KPa, stirred for 2-3h, stopped stirring, turned off the vacuum pump to release the vacuum, cooled to 70°C, discharged, and a hydrophilic cationic polyester polyether block copolymer is obtained; the mass ratio of dimethyl terephthalate, ethylene glycol, zinc acetate, polyethylene glycol 2000, di(hydroxyethyl)methyl dodecyl ammonium chloride, and antimony trioxide is 100-110:50-60:0.2-0.3:630-650:410-430:1.2-1.4;
[0031] A2. Mix the hydrophilic cationic polyester polyether block copolymer, deionized water and polyethylene glycol, and stir for 30-40 minutes to obtain the treatment solution D; the mass ratio of the hydrophilic cationic polyester polyether block copolymer, deionized water and polyethylene glycol is 1-2:5-8:1-2.
[0032] The breathable, cool and comfortable fabric is prepared by the preparation method.
[0033] Beneficial effects of the present invention:
[0034] The present invention discloses a breathable, cool and comfortable fabric and a preparation method thereof. The breathable and comfortable performance of the fabric is improved by selecting polyester-based coconut carbon fiber, polyester-based coffee carbon fiber and kiwano fiber with good air permeability, comfortable texture, cooling and antibacterial properties. In addition, gel capsules are covered on the surface of the fabric to further enhance the cooling and antibacterial properties of the fabric. Furthermore, a hydrophilic cationic polyester polyether block copolymer is covered on one side of the fabric to enhance the quick-drying performance of the fabric. DETAILED DESCRIPTION
[0035] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0036] Example 1
[0037] A method for preparing a breathable, cool and comfortable fabric comprises the following steps:
[0038] S1, taking polyester-based coconut carbon fiber, polyester-based coffee carbon fiber, and kiwano fiber to mix to obtain a mixed material, immersing the mixed material in treatment solution A for 25 hours, fishing out and shaking evenly, and using conventional technical means in the field to perform opening, carding, drawing, roving, spun yarn, and winding to obtain warp; the mass ratio of the polyester-based coconut carbon fiber, polyester-based coffee carbon fiber, kiwano fiber, and treatment solution A is 2:2:0.5:35;
[0039] The treatment liquid A is prepared by mixing crude oil AL-106 and deionized water in a volume ratio of 1:8.5;
[0040] S2, taking cotton fibers and performing cleaning, carding, drawing, roving, spinning, and winding using conventional techniques in the art to obtain weft yarns;
[0041] S3, using conventional technical means in the art to weave the warp and weft into a grid shape using a loom to form a grey cloth A; the mass ratio of the warp and weft is 7:3;
[0042] S4, immersing the grey cloth A in the treatment solution B, heating in a water bath at 90° C. for 40 min for alkali treatment, taking out and washing with water to obtain grey cloth B;
[0043] The treatment solution B is prepared by mixing sodium chloride, sodium hydroxide and deionized water in a mass ratio of 0.5:40:1000;
[0044] S5, immersing the grey cloth B in the treatment solution C, performing padding finishing at 40° C. for 40 min, and baking at 120° C. for 2 min to obtain the grey cloth C;
[0045] The preparation method of the treatment solution C comprises the following steps:
[0046] Sodium alginate, deionized water, Span 80, peppermint oil, and berry tea extract were mixed, homogenized at an emulsification speed of 10,000 rpm for 4 minutes, gelatin was added, the pH was adjusted to 4.2, homogenized at 45° C. at an emulsification speed of 10,000 rpm for 6 minutes, then cooled to 0° C. and allowed to stand for 0.5 hours, the pH was adjusted to 9, glutaraldehyde aqueous solution was added, allowed to stand at room temperature for 3 hours, polyacrylic acid was added, and stirred for 20 minutes to obtain the treatment solution C;
[0047] The mass ratio of the sodium alginate, deionized water, Span 80, peppermint oil, berry tea extract, gelatin, glutaraldehyde aqueous solution, and polyacrylic acid is 1:100:0.4:4:2:3:3:0.4; the mass fraction of the glutaraldehyde aqueous solution is 25%;
[0048] The preparation method of the berry tea extract comprises the following steps:
[0049] The bud tips of berry tea are extracted with ethanol aqueous solution under ultrasound, and the solvent is removed to obtain berry tea extract; 15 mL of ethanol aqueous solution is added to each gram of berry tea, the extraction temperature is 50°C, the extraction time is 30 minutes, and the concentration of the ethanol aqueous solution is 55%.
[0050] The average molecular weight of the polyacrylic acid is 2000;
[0051] S6, coating the treatment liquid D on one side of the grey fabric C, pre-baking at 80° C. for 2 min, and baking at 120° C. for 5 min, to obtain the breathable, cool and comfortable fabric;
[0052] The coating amount of the treatment liquid D is 15 g / m 2 ;
[0053] The preparation method of the treatment liquid D comprises the following steps:
[0054] A1. In a nitrogen atmosphere, dimethyl terephthalate, ethylene glycol and zinc acetate were added to a four-necked flask equipped with a thermometer, heated at 140°C for 30 min, heated to 180°C and stirred for 3 h, polyethylene glycol 2000, di(hydroxyethyl)methyl dodecyl ammonium chloride and antimony trioxide were added, and the temperature was slowly raised to 220°C. After keeping warm for 30 min, vaseline was applied to the interface of the device to ensure the sealing of the device and evacuation was started to a vacuum degree of -0.05 KPa, stirred for 2 h, stopped stirring, turned off the vacuum pump to unload the vacuum, cooled to 70°C, and discharged to obtain a hydrophilic cationic polyester polyether block copolymer; the mass ratio of dimethyl terephthalate, ethylene glycol, zinc acetate, polyethylene glycol 2000, di(hydroxyethyl)methyl dodecyl ammonium chloride and antimony trioxide was 100:50:0.2:630:410:1.2;
[0055] A2. Mix the hydrophilic cationic polyester polyether block copolymer, deionized water and polyethylene glycol, and stir for 30 minutes to obtain the treatment solution D; the mass ratio of the hydrophilic cationic polyester polyether block copolymer, deionized water and polyethylene glycol is 1:5:1.
[0056] Example 2
[0057] A method for preparing a breathable, cool and comfortable fabric comprises the following steps:
[0058] S1, taking polyester-based coconut carbon fiber, polyester-based coffee carbon fiber, and kiwano fiber to mix to obtain a mixed material, immersing the mixed material in treatment solution A for 30 hours, fishing out and shaking, opening, carding, drawing, roving, spun yarn, winding, and obtaining warp; the mass ratio of the polyester-based coconut carbon fiber, polyester-based coffee carbon fiber, kiwano fiber, and treatment solution A is 2.5:2.5:0.8:40;
[0059] The treatment liquid A is prepared by mixing crude oil AL-106 and deionized water in a volume ratio of 1:8.9;
[0060] S2, taking cotton fiber, cleaning, combing, drawing, roving, spun yarn, winding, and obtaining weft yarn;
[0061] S3, using a loom to weave the warp and weft into a grid shape to form a grey cloth A; the mass ratio of the warp and weft is 7:3;
[0062] S4, immersing the grey cloth A in the treatment solution B, heating in a water bath at 90° C. for 45 min for alkali treatment, taking out and washing with water to obtain grey cloth B;
[0063] The treatment solution B is prepared by mixing sodium chloride, sodium hydroxide and deionized water in a mass ratio of 0.5:40:1000;
[0064] S5, immersing the grey cloth B in the treatment solution C, padding and finishing at 40° C. for 50 min, and baking at 120° C. for 2.5 min to obtain the grey cloth C;
[0065] The preparation method of the treatment solution C comprises the following steps:
[0066] Sodium alginate, deionized water, Span 80, peppermint oil and berry tea extract were mixed, homogenized at an emulsification speed of 10000 rpm for 4.5 min, gelatin was added, the pH was adjusted to 4.3, homogenized at 45° C. at an emulsification speed of 10000 rpm for 7 min, then cooled to 5° C. and allowed to stand for 0.5 h, the pH was adjusted to 9.5, glutaraldehyde aqueous solution was added, and allowed to stand at room temperature for 3.5 h, polyacrylic acid was added, and stirred for 25 min to obtain the treatment solution C;
[0067] The mass ratio of the sodium alginate, deionized water, Span 80, peppermint oil, berry tea extract, gelatin, glutaraldehyde aqueous solution, and polyacrylic acid is 1.1:100:0.5:4.5:2.5:3.5:3.5:0.55; the mass fraction of the glutaraldehyde aqueous solution is 25%;
[0068] The preparation method of the berry tea extract comprises the following steps:
[0069] The bud tips of berry tea are extracted with ethanol aqueous solution under ultrasound, and the solvent is removed to obtain berry tea extract; 20 mL of ethanol aqueous solution is added to each gram of berry tea, the extraction temperature is 65°C, the extraction time is 40 minutes, and the concentration of the ethanol aqueous solution is 65%.
[0070] The average molecular weight of the polyacrylic acid is 2000;
[0071] S6, coating the treatment liquid D on one side of the grey fabric C, pre-baking at 80° C. for 2.5 min, and baking at 120° C. for 5.5 min, to obtain the breathable, cool and comfortable fabric;
[0072] The coating amount of the treatment liquid D is 21g / m 2 ;
[0073] The preparation method of the treatment liquid D comprises the following steps:
[0074] A1. In a nitrogen atmosphere, dimethyl terephthalate, ethylene glycol and zinc acetate were added to a four-necked flask equipped with a thermometer, heated at 145°C for 35 min, heated to 180°C and stirred for 3.5 h, polyethylene glycol 2000, di(hydroxyethyl)methyl dodecyl ammonium chloride and antimony trioxide were added, and the temperature was slowly raised to 230°C. After keeping warm for 30 min, vaseline was applied to the interface of the device to ensure the sealing of the device and evacuation was started to a vacuum degree of -0.05 KPa, stirred for 2.5 h, stopped stirring, turned off the vacuum pump to unload the vacuum, cooled to 70°C, and discharged to obtain a hydrophilic cationic polyester polyether block copolymer; the mass ratio of dimethyl terephthalate, ethylene glycol, zinc acetate, polyethylene glycol 2000, di(hydroxyethyl)methyl dodecyl ammonium chloride and antimony trioxide was 105:55:0.25:640:420:1.3;
[0075] A2. Mix the hydrophilic cationic polyester polyether block copolymer, deionized water and polyethylene glycol, and stir for 35 minutes to obtain the treatment solution D; the mass ratio of the hydrophilic cationic polyester polyether block copolymer, deionized water and polyethylene glycol is 1.5:6.5:1.5.
[0076] Example 3
[0077] A method for preparing a breathable, cool and comfortable fabric comprises the following steps:
[0078] S1, taking polyester-based coconut carbon fiber, polyester-based coffee carbon fiber, and kiwano fiber to mix to obtain a mixed material, immersing the mixed material in treatment solution A for 35 hours, fishing out and shaking, opening, carding, drawing, roving, spun yarn, winding, and obtaining warp; the mass ratio of the polyester-based coconut carbon fiber, polyester-based coffee carbon fiber, kiwano fiber, and treatment solution A is 3:3:1:45;
[0079] The treatment liquid A is prepared by mixing crude oil AL-106 and deionized water in a volume ratio of 1:9.2;
[0080] S2, taking cotton fiber, cleaning, combing, drawing, roving, spun yarn, winding, and obtaining weft yarn;
[0081] S3, using a loom to weave the warp and weft into a grid shape to form a grey cloth A; the mass ratio of the warp and weft is 7:3;
[0082] S4, immersing the grey cloth A in the treatment solution B, heating in a water bath at 90° C. for 50 min for alkali treatment, taking out and washing with water to obtain grey cloth B;
[0083] The treatment solution B is prepared by mixing sodium chloride, sodium hydroxide and deionized water in a mass ratio of 0.5:40:1000;
[0084] S5, immersing the grey cloth B in the treatment solution C, padding and finishing at 40° C. for 60 min, and baking at 120° C. for 3 min to obtain the grey cloth C;
[0085] The preparation method of the treatment solution C comprises the following steps:
[0086] Sodium alginate, deionized water, Span 80, peppermint oil and berry tea extract were mixed, homogenized at an emulsification speed of 10,000 rpm for 5 minutes, gelatin was added, the pH was adjusted to 4.4, homogenized at 45° C. at an emulsification speed of 10,000 rpm for 8 minutes, then cooled to 10° C. and allowed to stand for 0.5 hours, the pH was adjusted to 10, glutaraldehyde aqueous solution was added, and allowed to stand at room temperature for 3-4 hours, polyacrylic acid was added, and stirred for 30 minutes to obtain the treatment solution C;
[0087] The mass ratio of the sodium alginate, deionized water, Span 80, peppermint oil, berry tea extract, gelatin, glutaraldehyde aqueous solution, and polyacrylic acid is 1.2:100:0.6:5:3:4:4:0.7; the mass fraction of the glutaraldehyde aqueous solution is 25%;
[0088] The preparation method of the berry tea extract comprises the following steps:
[0089] The bud tips of berry tea are extracted with ethanol aqueous solution under ultrasound, and the solvent is removed to obtain berry tea extract; 25 mL of ethanol aqueous solution is added to each gram of berry tea, the extraction temperature is 70°C, the extraction time is 50 minutes, and the concentration of the ethanol aqueous solution is 75%.
[0090] The average molecular weight of the polyacrylic acid is 2000;
[0091] S6, coating the treatment liquid D on one side of the grey fabric C, pre-baking at 80° C. for 3 min, and baking at 120° C. for 6 min, to obtain the breathable, cool and comfortable fabric;
[0092] The coating amount of the treatment liquid D is 27 g / m 2 ;
[0093] The preparation method of the treatment liquid D comprises the following steps:
[0094] A1. In a nitrogen atmosphere, dimethyl terephthalate, ethylene glycol and zinc acetate were added to a four-necked flask equipped with a thermometer, heated at 150°C for 40 min, heated to 180°C and stirred for 4 h, polyethylene glycol 2000, di(hydroxyethyl)methyl dodecyl ammonium chloride and antimony trioxide were added, and the temperature was slowly raised to 240°C. After keeping warm for 30 min, vaseline was applied to the interface of the device to ensure the sealing of the device and evacuation was started to a vacuum degree of -0.05 KPa, stirred for 3 h, stopped stirring, turned off the vacuum pump to unload the vacuum, cooled to 70°C, and discharged to obtain a hydrophilic cationic polyester polyether block copolymer; the mass ratio of dimethyl terephthalate, ethylene glycol, zinc acetate, polyethylene glycol 2000, di(hydroxyethyl)methyl dodecyl ammonium chloride and antimony trioxide was 110:60:0.3:650:430:1.4;
[0095] A2. Mix the hydrophilic cationic polyester polyether block copolymer, deionized water and polyethylene glycol, and stir for 40 minutes to obtain the treatment solution D; the mass ratio of the hydrophilic cationic polyester polyether block copolymer, deionized water and polyethylene glycol is 2:8:2.
[0096] Comparative Example 1
[0097] The difference from Example 2 is that the mass ratio of the polyester-based coconut carbon fiber, the polyester-based coffee carbon fiber and the kiwano fiber in the mixed material in step S1 is 5:0:0.8.
[0098] Comparative Example 2
[0099] The difference from Example 2 is that the mass ratio of the polyester-based coconut carbon fiber, the polyester-based coffee carbon fiber and the kiwano fiber in the mixed material in step S1 is 0:5:0.8.
[0100] Comparative Example 3
[0101] The difference from Example 2 is that the mass ratio of the polyester-based coconut carbon fiber, the polyester-based coffee carbon fiber and the kiwano fiber in the mixed material in step S1 is 2.5:3.3:0.
[0102] Comparative Example 4
[0103] The difference from Example 2 is that the method for preparing the breathable, cool and comfortable fabric comprises the following steps:
[0104] S1, taking polyester-based coconut carbon fiber, polyester-based coffee carbon fiber, and kiwano fiber to mix to obtain a mixture, immersing the mixture in treatment solution A for 30 hours, fishing out and shaking, opening, carding, drawing, roving, spun yarn, winding, and obtaining warp;
[0105] S2, taking cotton fiber, cleaning, combing, drawing, roving, spun yarn, winding, and obtaining weft yarn;
[0106] S3, weaving the warp and weft into a grid shape using a loom to form a grey cloth A;
[0107] S4, immersing the grey cloth A in the treatment solution B, heating in a water bath at 90° C. for 45 min for alkali treatment, taking out and washing with water to obtain grey cloth B;
[0108] S5, coating the treatment liquid D on one side of the grey fabric B, pre-baking at 80° C. for 2.5 min, and baking at 120° C. for 5.5 min, to obtain the breathable, cool and comfortable fabric;
[0109] Comparative Example 5
[0110] The difference from Example 2 is that peppermint oil is not added during the preparation of the treatment liquid C.
[0111] Comparative Example 6
[0112] The difference from Example 2 is that no berry tea extract is added during the preparation of the treatment solution C.
[0113] Comparative Example 7
[0114] The difference from Example 2 is that in step S6, the treatment liquid D is coated on both sides of the grey cloth C.
[0115] Comparative Example 8
[0116] The difference from Example 2 is that the grey cloth C is not coated with the treatment liquid D in step S6.
[0117] Performance Testing
[0118] Test Example 1
[0119] Conduct air permeability test according to standard GB / T5453-1997;
[0120] Conduct cooling performance test according to standard GB / T 35263-2017;
[0121] The antibacterial performance test was carried out in accordance with the standard GB / T39104.2-2020.
[0122] The fabrics obtained in Examples 1-3 and Comparative Examples 1-6 prepared on the basis of Example 2 were subjected to performance tests according to the above standards. The test results are shown in Table 1 below:
[0123] Table 1
[0124]
[0125]
[0126] As can be seen from Table 1, the fabrics prepared in Examples 1-3 of the present application have excellent air permeability, a cool texture, and an antibacterial effect.
[0127] In Comparative Example 1, polyester-based coffee carbon fiber was not added, resulting in reduced air permeability and cooling performance; in Comparative Example 2, polyester-based coconut carbon fiber was not added, resulting in reduced air permeability and cooling performance; in Comparative Example 3, kiwano fiber was not added, resulting in reduced air permeability and cooling performance; this is because the materials of polyester-based coconut carbon fiber, polyester-based coffee carbon fiber, and kiwano fiber have excellent air permeability and cool texture, and the three synergistically improve the air permeability and cooling comfort performance of the fabric. The cool gel capsules in Comparative Examples 4-6 have almost no effect on the air permeability, but the fabric surface in Comparative Example 4 is not covered with gel capsules, resulting in a significant reduction in cooling. No peppermint oil was added in Comparative Example 5, and no berry tea extract was added in Comparative Example 6. The volatilization of peppermint oil and berry tea extract will take away heat due to the cooling effect, thereby improving the cooling performance of the fabric.
[0128] In addition, in terms of antibacterial properties, polyester-based coffee carbon fiber was not added to Comparative Example 1, resulting in reduced antibacterial properties; in Comparative Example 2, polyester-based coconut carbon fiber was not added, resulting in reduced antibacterial properties; in Comparative Example 3, caltrop fiber was not added, resulting in reduced antibacterial properties; this is because polyester-based coconut carbon fiber, polyester-based coffee carbon fiber, and caltrop fiber have certain antibacterial effects, and the three synergistically improve the antibacterial properties;
[0129] In Comparative Example 4, the surface of the fabric was not covered with gel capsules, resulting in reduced antibacterial performance; in Comparative Example 5, peppermint oil was not added, resulting in reduced antibacterial performance; in Comparative Example 6, berry tea extract was not added, resulting in reduced antibacterial performance; this is because peppermint oil and berry tea extract contain a large amount of antibacterial volatile substances, which can improve the antibacterial performance of the fabric.
[0130] Test Example 2
[0131] The quick-drying performance of Examples 1-3 and Comparative Examples 4, 7 and 8 was tested, and the test results are shown in Table 2 below.
[0132] Table 2
[0133] Water evaporation rate (g / h) Example 1 0.385 Example 2 0.391 Example 3 0.384 Comparative Example 4 0.379 Comparative Example 7 0.242 Comparative Example 8 0.313
[0134] As can be seen from Table 2, the present application improves the hydrophilicity of the fabric by coating a hydrophilic cationic polyester polyether block copolymer on one side of the fabric, so that the fabric forms a one-sided water guide channel, improves the quick-drying effect, and avoids moisture accumulation that causes the fabric to stick to the skin and create a sticky, stuffy and uncomfortable feeling.
[0135] Test Example 3
[0136] Examples 1-3 and Comparative Example 4 were tested for washability, and the test results are shown in Table 3 below.
[0137] Table 3
[0138] Water evaporation rate (g / h) Example 1 0.367 Example 2 0.372 Example 3 0.369 Comparative Example 4 0.337
[0139] It can be seen from Table 3 that the fabrics prepared in Examples 1-3 of the present application have excellent wash resistance compared to the comparative example 4 without the addition of gel capsules. This is because the gel capsules of the present application act as connecting adhesives to enhance the adhesion of the hydrophilic cationic polyester polyether block copolymer on the surface of the fabric, thereby improving the wash resistance of the fabric and maintaining the durability of the quick-drying performance.
[0140] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a breathable, cool and comfortable fabric, characterized in that: The following steps are involved: S1, taking polyester-based coconut carbon fiber, polyester-based coffee carbon fiber, and kiwano fiber and mixing them, immersing them in treatment solution A, taking them out and shaking them evenly, opening them, combing them, drawing them, roving them, spun them, winding them, and obtaining warp yarns; S2, taking cotton fiber, cleaning, combing, drawing, roving, spun yarn, winding, and obtaining weft yarn; S3, weaving the warp and weft into a grid shape using a loom to form a grey cloth A; S4, immersing the grey cloth A in the treatment solution B, heating in a water bath for alkali treatment, taking out and washing with water to obtain the grey cloth B; S5, immersing the grey cloth B in the treatment solution C, performing padding finishing, and baking to obtain the grey cloth C; S6. Coat the treatment liquid D on one side of the grey cloth C and bake it to obtain the breathable, cool and comfortable fabric.
2. The method for preparing a breathable, cool and comfortable fabric according to claim 1, characterized in that: In step S1, the mass ratio of the polyester-based coconut carbon fiber, polyester-based coffee carbon fiber, kiwano fiber, and treatment liquid A is 2-3:2-3:0.5-1:35-45.
3. The method for preparing a breathable, cool and comfortable fabric according to claim 1, characterized in that: In step S1, the treatment liquid A is prepared by mixing crude oil AL-106 and deionized water in a volume ratio of 1:8.5-9.
2.
4. The method for preparing a breathable, cool and comfortable fabric according to claim 1, characterized in that: In step S3, the mass ratio of the warp and weft is 7:
3.
5. The method for preparing a breathable, cool and comfortable fabric according to claim 1, characterized in that: In step S4, the treatment solution B is prepared from sodium chloride, sodium hydroxide, and deionized water in a mass ratio of 0.5:40:1000.
6. The method for preparing a breathable, cool and comfortable fabric according to claim 1, characterized in that: In step S5, the method for preparing the treatment solution C comprises the following steps: Sodium alginate, deionized water, Span 80, peppermint oil and berry tea extract were mixed, homogenized at an emulsification speed of 10,000 rpm for 4-5 minutes, gelatin was added, the pH was adjusted to 4.2-4.4, homogenized at 45° C. at an emulsification speed of 10,000 rpm for 6-8 minutes, then cooled to 0-10° C. and allowed to stand for 0.5 hours, the pH was adjusted to 9-10, glutaraldehyde aqueous solution was added, and the mixture was allowed to stand at room temperature for 3-4 hours, polyacrylic acid was added, and stirred for 20-30 minutes to obtain the treatment solution C.
7. The method for preparing a breathable, cool and comfortable fabric according to claim 6, characterized in that: The mass ratio of the sodium alginate, deionized water, Span 80, peppermint oil, berry tea extract, gelatin, glutaraldehyde aqueous solution, and polyacrylic acid is 1-1.2:100:0.4-0.6:4-5:2-3:3-4:3-4:0.4-0.7; the mass fraction of the glutaraldehyde aqueous solution is 25%.
8. The method for preparing a breathable, cool and comfortable fabric according to claim 6, characterized in that: The preparation method of the berry tea extract comprises the following steps: The bud tips of berry tea are extracted with ethanol aqueous solution under ultrasound, and the solvent is removed to obtain berry tea extract; 15-25 mL of ethanol aqueous solution is added to each gram of berry tea, the extraction temperature is 50-70°C, the extraction time is 30-50 minutes, and the concentration of the ethanol aqueous solution is 55-75%.
9. The method for preparing a breathable, cool and comfortable fabric according to claim 1, characterized in that: In step S6, the method for preparing the treatment liquid D comprises the following steps: The hydrophilic cationic polyester polyether block copolymer, deionized water and polyethylene glycol are mixed and stirred for 30-40 minutes to obtain the treatment solution D; the mass ratio of the hydrophilic cationic polyester polyether block copolymer, deionized water and polyethylene glycol is 1-2:5-8:1-2.
10. A breathable, cool and comfortable fabric made by the preparation method according to any one of claims 1 to 9.